1989
DOI: 10.1152/ajpheart.1989.257.6.h1958
|View full text |Cite
|
Sign up to set email alerts
|

Dilator response of rat mesenteric arcading arterioles to increased blood flow velocity

Abstract: Arcading arterioles (average diam 68 microns ID) connecting adjacent triangular vascular sectors in the rat mesentery were examined in vivo for the presence of flow-dependent vasodilation. When a feed artery to one of these sectors was occluded, the affected sector was supplied by collateral flow through the arcading arteriole, and red cell velocity in the arteriole increased by 10-66 mm/s. The velocity increase was followed (with an average delay of 7.7 s) by dilation of the arcading arteriole, which averaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 0 publications
4
71
1
Order By: Relevance
“…The parameter governing shear-dependent sensitivity was assumed to be equal in both arteriolar segments. It has been observed that the shear-dependent response is greater in small arteries and large arterioles than in small arterioles (18,32), and thus this model may overestimate the shear-dependent response in small arterioles. NO scavenging by RBCs is not considered in the model, causing a possibly greater overestimation of the shear stress contribution to autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter governing shear-dependent sensitivity was assumed to be equal in both arteriolar segments. It has been observed that the shear-dependent response is greater in small arteries and large arterioles than in small arterioles (18,32), and thus this model may overestimate the shear-dependent response in small arterioles. NO scavenging by RBCs is not considered in the model, causing a possibly greater overestimation of the shear stress contribution to autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…flow rate; furthermore, this effect was blocked by LNMMA, but not by indomethacin. Although most reports of flowinduced dilation suggest mediation by NO (3,12,13), some have reported a role for endothe lium-der ived eicosanoids (4). Cyclooxygenase products did not appear to mediate this phenomenon in newborn intestine.…”
Section: Discussionmentioning
confidence: 99%
“…If so, one role of these nitrergic neurons could be to detect distortion from moving internal fluids by way of stretch receptors and to transmit output signals to other neurons or musculo-epithelial cells thereby directly adjusting muscle tension levels and peristalsis. This postulated mechanism has some analogy with the shearing forces acting on the luminal surface of mammalian vascular endothelium to regulate the release of NO (Buga et al, 1991;Smiesko et al, 1989). The location of these neurons in the tentacles and oral disc also suggest a role in feeding, but preliminary experiments with NO donors and NOS inhibitors failed to affect the posture of tentacles or mouth opening.…”
Section: Histochemistry Of Putative Nos-containing Cellsmentioning
confidence: 93%